2007
DOI: 10.1007/s00015-007-1231-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of authigenic albites in a limestone succession of the Helvetic Domain, eastern Switzerland

Abstract: A new occurrence of authigenic albite was found in a Jurassic sedimentary succession of the Glarus Nappe near Walenstadt (eastern Switzerland). The euhedral shape and the chemical purity of these albites are evidence for their authigenic origin. The crystals are irregularly distributed in the sediment, highlighting the importance of the host rock composition for albite authigenesis. The crystals occur exclusively in limestones with a carbonate content higher than 80 wt-%. A diagenetic or hydrothermal origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Although rarely abundant volumetrically, these albite crystals are widespread within the investigated Harderode and Haddessen samples and no K-or Ca-feldspars have been observed. Based on these characteristics, following Kastner and Siever (1979), Spötl et al (1999), Rais et al (2008) and Bernard et al (2010a), the albite crystals described here might be identified as authigenic feldspars. Not strictly synonymous with diagenesis, authigenesis is commonly used in the literature when referring to minerals that formed in-situ during either high-grade diagenesis or low-grade metamorphism (Kastner and Siever, 1979;Spötl et al, 1999).…”
Section: Implications Of the Mineral Assemblage For The Thermal Histomentioning
confidence: 95%
“…Although rarely abundant volumetrically, these albite crystals are widespread within the investigated Harderode and Haddessen samples and no K-or Ca-feldspars have been observed. Based on these characteristics, following Kastner and Siever (1979), Spötl et al (1999), Rais et al (2008) and Bernard et al (2010a), the albite crystals described here might be identified as authigenic feldspars. Not strictly synonymous with diagenesis, authigenesis is commonly used in the literature when referring to minerals that formed in-situ during either high-grade diagenesis or low-grade metamorphism (Kastner and Siever, 1979;Spötl et al, 1999).…”
Section: Implications Of the Mineral Assemblage For The Thermal Histomentioning
confidence: 95%
“…Motivated by this suggestion, other studies have subsequently documented minor but common occurrence of low-temperature feldspars in carbonate rocks and sandstones (e.g., Hearn and Sutter, 1985;Molenaar and de Jong, 1987;Ramseyer et al, 1993;Spötl et al, 1999;Rais et al, 2008). There have been two models proposed to explain the low-temperature feldspar authigenesis: (a) isochemical transformation (Kastner and Siever, 1979), and (b) the interaction between migrating brine and host rocks (Hearn and Sutter, 1985;Spötl et al, 1999;Rais et al, 2008). In the isochemical transformation model, authigenic feldspar forms through the burial transformation of pre-existing detrital minerals in sediments.…”
Section: Low-temperature Feldspar Formationmentioning
confidence: 92%
“…If the sediment itself serves as the essential donor of all constituents for feldspar authigenesis, authigenic feldspar should be expected to be a common mineral in sedimentary rocks. In contrast, the interaction model between migrating brines and host rocks proposes that the cations (Na, K and Ca) in feldspar are derived from saline fluids, and other constituents of feldspar are supplied from siliciclastic debris (e.g., clay minerals) within host rocks (Rais et al, 2008). However, an experimental study by Small (1994) showed that the formation of feldspar through the reaction between saline solution and smectite required high temperature and pressure (200°C and 50 MPa).…”
Section: Low-temperature Feldspar Formationmentioning
confidence: 95%
See 1 more Smart Citation
“…Kastner (1971) also cites the importance of ions from sea water in the formation of albite at low temperatures. Kastner (1971) and Rais (2008) linked clay diagenesis to the formation of albite. The albite in the lithoclasts in the Wolfcamp probably formed from internal fluids on the platform before being subaerially exposed and eroded.…”
Section: Lithoclast Diagenesismentioning
confidence: 99%